CELEBRITY ENDORSEMENT, PACKAGING DESIGN, AND BRAND IMAGE: WARDAH'S STRATEGY TO WIN CONSUMERS' HEARTS IN SEMARANG - Khairunnisa, Widarahma Agestha; Putra , Febrianur Ibnu Fitroh Sukono; Anomsari , Ariati; Farida, Ida (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Indonesia has a high level of consumption, driven by increasing purchasing power. Competition between manufacturers is also intensifying due to the large number of similar products on the market. According to data from the Ministry of Home Affairs' Population and Civil Registration Agency (Dukcapil), Indonesia's population reached 273 million at the end of 2021, with approximately 49.5% being women. Many women are striving to improve their appearance to boost their self-confidence, leading to rapid growth in the cosmetics industry and significant growth in Indonesia.Methods: This research uses a descriptive, quantitative approach, applying survey methods by taking samples from a population and using questionnaires as the primary instrument to collect data.Celebrity endorsements do not significantly influence purchasing decisions for Wardah products, while packaging Design and brand image do.Result: This finding is implemented in the context of marketing Wardah cosmetic products, which places great importance on the product’s visual elements and on consistent brand image management, and is more effective at attracting consumer interest than celebrity appeal. Therefore, the company is strongly advised to focus on developing the visual packaging Design aspect of its marketing strategy and to build a more positive brand image that is relevant to the values that consumers of Wardah products need. Keyword: Brand Image, Celebrity Endorsement, Packaging Design, and Purchase Decision